2006
DOI: 10.1159/000093922
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Delusion Proneness and Personality Structure in Non-Clinical Participants: Comparison between Young and Elderly Samples

Abstract: Background: Few studies have explored the prevalence of delusions in the non-clinical, elderly population. In addition, the association between personality structure and delusions remains poorly investigated. The aims of the present study were, first, to explore the relation between age and the prevalence of delusion proneness and, second, to examine the association between personality and delusion proneness in young and elderly participants. Sampling and Methods: A sample of young (n = 343; aged 18–30 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 110 publications
(89 reference statements)
0
14
0
Order By: Relevance
“…The same results were shown in the British National Psychiatric Morbidity Survey [4], in which there was a significant association between age and paranoid thoughts and no association between age and psychotic and hallucinatory experiences. Indeed, the dimensional view of the correlation between the intensity of psychotic symptoms and age, which has some supporting evidence [24,41], requires more attention in future studies. …”
Section: Discussionmentioning
confidence: 99%
“…The same results were shown in the British National Psychiatric Morbidity Survey [4], in which there was a significant association between age and paranoid thoughts and no association between age and psychotic and hallucinatory experiences. Indeed, the dimensional view of the correlation between the intensity of psychotic symptoms and age, which has some supporting evidence [24,41], requires more attention in future studies. …”
Section: Discussionmentioning
confidence: 99%
“…* p<0.01, ** p<0.001. Krabbendam et al 2002 ;Lysaker et al 2003 ;Horan et al 2005 ;Laroi et al 2006). Moreover, one study reported a moderating effect of neuroticism on the association between positive schizotypy and measures of psychopathology and functioning in a non-clinical sample (Barrantes-Vidal et al 2009).…”
Section: Psychological Mechanismsmentioning
confidence: 99%
“…We choose to use the FFM and NEO-PI-R because of the widespread use of both in the research literature and because many human resource practitioners are familiar with the NEO-PI-R (Furnham, 2008). In addition, prior research has demonstrated the effectiveness of using composites of FFM facets to predict other criteria of interest including behavioral aggression (e.g., Gudonis, Miller, Miller, & Lynam, 2008;Lari, Van der Linden, DeFruyt, Van Os, & Aleman, 2006). In selecting facet-level FFM traits for the examined motivational composite, we began with a rational method of relating trait descriptions to behavioral self-regulation outcomes.…”
Section: Selection Of Ffm Facet-level Traits For the Motivational Commentioning
confidence: 99%